Environmental drivers of coral reef carbonate production and bioerosion: a multi‐scale analysis. Issue 10 (22nd August 2017) - Silbiger, Nyssa J.; Donahue, Megan J.; Brainard, Russell E.
Abstract: The resilience of coral reefs depends on the balance between reef growth and reef breakdown, and their responses to changing environmental conditions. Across the 2500‐km Hawaiian Archipelago, we quantified rates of carbonate production, bioerosion, and net accretion at regional, island, site, and within‐site spatial scales and tested how these rates respond to environmental conditions across different spatial scales. Overall, there were four major outcomes from this study: (1) bioerosion rates were generally higher in the populated Main Hawaiian Islands (MHI) than the remote, protected Northwestern Hawaiian Islands (NWHI), while carbonate production rates did not vary significantly between the two regions; (2) variability in carbonate production, bioerosion, and net accretion rates was greatest at the smallest within‐reef spatial scale; (3) carbonate production and bioerosion rates were associated with distinct sets of environmental parameters; and (4) the strongest correlates of carbonate production, bioerosion, and net accretion rates were different between the MHI region and the NWHI region: in the MHI, the dominant correlates were percent cover of macroalgae and herbivorous fish biomass for carbonate production and bioerosion, respectively, whereas in the NWHI, the top correlates were total alkalinity and benthic cover. This study highlights the need to understand accretion and erosion processes as well as local environmental conditions to predict net coral reef responses to future environmental changes.